A decade of progress in type 2 diabetes and cardiovascular disease: advances in SGLT2 inhibitors and GLP-1 receptor agonists – a comprehensive review - Aristizábal-Colorado, David; Corredor-Rengifo, David; Sierra-Castillo, Santiago; López-Corredor, Carolina; Vernaza-Trujillo, David-Alexander; Weir-Restrepo, Danilo; Izquierdo-Condoy, Juan S.; Ortiz-Prado, Esteban; Rico-Fontalvo, Jorge; Gómez-Mesa, Juan-Esteban; Abreu-Lomba, Alin; Rivera-Martínez, Wilfredo-Antonio (Frontiers in Endocrinology, 2025)
Cardiovascular and renal complications remain leading causes of morbidity and mortality among individuals with type 2 diabetes mellitus (T2DM). Since 2015, large-scale cardiovascular outcome trials (CVOTs) have demonstrated that sodium-glucose cotransporter-2 inhibitors (SGLT2i) and glucagon-like peptide-1 receptor agonists (GLP-1 RAs) significantly reduce the risk of major adverse cardiovascular events, cardiovascular mortality, and heart failure hospitalization in patients with T2DM and established cardiovascular disease or high-risk profiles. These findings—originating from landmark trials such as EMPA-REG OUTCOME, LEADER, and SUSTAIN-6—have led to substantial revisions in international guidelines from the European Society of Cardiology, American College of Cardiology, and American Heart Association, which now recommend the use of SGLT2i or GLP-1 RAs, often in conjunction with metformin. SGLT2i have shown robust effects in reducing heart failure hospitalization and slowing the progression of chronic kidney disease, while GLP-1 RAs have demonstrated superior efficacy in reducing atherothrombotic events, particularly non-fatal stroke. Additionally, emerging data supports the complementary use of both drug classes, revealing additive benefits on cardiovascular and renal outcomes without increased toxicity. This narrative review summarizes the mechanisms of action, clinical efficacy, safety profiles, and sex-specific outcomes associated with SGLT2i and GLP-1 RAs. It also highlights key evidence supporting their combined use and underscores their critical role in optimizing long-term outcomes in patients with T2DM and cardiovascular disease.